Patógenos e indicadores microbiológicos de calidad del agua para consumo humano (2017)
ABSTRACT: Upgrading water supplies is an opportunity to resolve health care problems. Thus, this shows the importance of establishing comprehensive evaluation and management models to guarantee quality. Currently, there are numerous methodologies to detect microbial water contamination. Nevertheless, the high cost, which analysis time and isolation in microorganism cultures represent, has been an obstacle to establish microbial water quality for human consumption. The use of microorganisms that are bio indicators of water quality decreases costs and facilitates the implementation of efficient treatment measures, water control and control of diseases associated to transmission. The objective of the review was to describe the main microbiological indicators used to evaluate drinking water as key items to propose a new monitoring schema in Colombia. Results reflect the need to consider some microbial agents that were previously not considered like viruses and other bacteria and parasites, bio indicators, in addition to bacteria and protozoans already established in the norm. On the other hand, they indicate the need to establish reference values and define the microorganisms, which will be used based on specific evaluations of the microbial situation of the water in monitoring to validate, operate and verify. This review contributes important information to update Colombian norms based on knowledge of international, national and local standards.